2015
DOI: 10.1007/s00192-015-2737-2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal strength in voiding cystometry: a risk factor for recurrent urinary tract infections in women

Abstract: Abdominal strength in the voiding phase constitutes a risk factor for recurrent urinary tract infections in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The characteristics of excluded studies: 11 studies were excluded after the review of the full manuscript. Data was not extractable in 2 studies [20,21]. One study was focusing at the incidence of recurrent UTIs and did not report on investigation findings [2].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The characteristics of excluded studies: 11 studies were excluded after the review of the full manuscript. Data was not extractable in 2 studies [20,21]. One study was focusing at the incidence of recurrent UTIs and did not report on investigation findings [2].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Another datum of note derived from our study is the relationship between abdominal straining during voiding and bladder lithiasis. Salinas et al 16 verified a relationship between increased voiding abdominal straining and recurrent UTI in women. It is possible that the same mechanism might intervene in the formation of bladder calculi in patients with SCI by fostering UTI.…”
Section: Discussionmentioning
confidence: 97%
“…Postmenopausal women with recurrent UTI had a significantly increased RU and reduced urine flow compared with age-matched controls [ 44 45 ]. A urodynamic study also found increased abdominal strength in voiding which constitutes a risk factor for recurrent UTI in women [ 46 ]. The ideal cutoff point for the maximum abdominal pressure in the voiding phase was 28 cmH 2 O.…”
Section: R Isk Factorsmentioning
confidence: 99%